Inherited variation in circadian rhythm genes and risks of prostate cancer and three other cancer sites in combined cancer consortia. Issue 9 (29th July 2017) - Gu, Fangyi; Zhang, Han; Hyland, Paula L.; Berndt, Sonja; Gapstur, Susan M.; Wheeler, William; ELLIPSE consortium*, the; Amos, Christopher I.; Bezieau, Stephane; Bickeböller, Heike; Brenner, Hermann; Brennan, Paul; et al.
Abstract : Circadian disruption has been linked to carcinogenesis in animal models, but the evidence in humans is inconclusive. Genetic variation in circadian rhythm genes provides a tool to investigate such associations. We examined associations of genetic variation in nine core circadian rhythm genes and six melatonin pathway genes with risk of colorectal, lung, ovarian and prostate cancers using data from the Genetic Associations and Mechanisms in Oncology (GAME‐ON) network. The major results for prostate cancer were replicated in the Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial, and for colorectal cancer in the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO). The total number of cancer cases and controls was 15, 838/18, 159 for colorectal, 14, 818/14, 227 for prostate, 12, 537/17, 285 for lung and 4, 369/9, 123 for ovary. For each cancer site, we conducted gene‐based and pathway‐based analyses by applying the summary‐based Adaptive Rank Truncated Product method (sARTP) on the summary association statistics for each SNP within the candidate gene regions. Aggregate genetic variation in circadian rhythm and melatonin pathways were significantly associated with the risk of prostate cancer in data combining GAME‐ON and PLCO, after Bonferroni correction ( p pathway  < 0.00625). The two most significant genes were NPAS2 ( p gene  = 0.0062) and AANAT ( p gene  = 0.00078); the latter being significant after Bonferroni correction. For colorectal cancer, we observed a suggestive association with the circadian rhythm pathway in GAME‐ON ( p pathway  = 0.021); this association was not confirmed in GECCO ( p pathway  = 0.76) or the combined data ( p pathway  = 0.17). No significant association was observed for ovarian and lung cancer. These findings support a potential role for circadian rhythm and melatonin pathways in prostate carcinogenesis. Further functional studies are needed to better understand the underlying biologic mechanisms. Abstract : What's new? Circadian disruption has been linked to carcinogenesis in animal models, but the evidence in humans is inconclusive. In this large SNP study, the authors found a significant association between both circadian‐rhythm and melatonin‐pathway gene variants and prostate‐cancer risk. These results support a role for circadian‐rhythm and melatonin pathways in prostate carcinogenesis.